Outpatient Transurethral Cystolithotripsy of Large Bladder Stones by Holmium Laser - Karami, Hosein; Razaghi, Moahammad Reza; Javanmard, Babak; Yaghoobi, Mohammad; Hasanzadeh Hadad, Amin; Amani, Maryam; Golmohammadi Taklimi, Amin (Journal of Lasers in Medical Sciences, 2016)
Introduction: To assessment of the efficacy and safety of transurethral cystolithotripsy of large bladder stones by holmium laser in the outpatient setting. Methods: In a prospective study, 48 consecutive adult patients with large bladder stones, were enrolled for transurethral cystolithotripsy. Patients older than 18 years, with bladder stones larger than 2 cm were enrolled. Urethral stricture, active urinary infection, and any anesthetic contraindications for operation, were the exclusion criteria. Demographic characteristics of patients, outcomes and complications related to operation and post operation period, were recorded. Results: Patients mean age was 46 ± 7.3 years. Male to female ratio was 45/3. Mean body mass index of patients was 28.5 ± 3.5. Mean stone size was 3.7 ± 1.6 cm. Mean operation time was 43.5 ± 15.5 minutes. Nearly complete stone clearance (98.5%) was achieved in all patients. Mean hospital stay was 6.5 ± 1.3 hours. No major complications were seen. Mean visual analog pain score (VAS) was 4.2 ± 2.1 and 1.4 ± 0.6, during and 1 hour after operation, respectively. During follow up of 22.4 ± 12.5 months, recurrence of bladder stone was not seen. No case of urethral stricture was detected. Conclusion: Transurethral holmium laser lithotripsy is an effective and safe alternative in selected patients with large bladder stones. This procedure can be easily performed in the outpatient setting.